1999
DOI: 10.1016/s0022-5223(99)70220-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural valve deterioration in mitral replacement surgery: Comparison of carpentier-edwards supra-annular porcine and perimount pericardial bioprostheses

Abstract: Background: Bioprostheses preserved with glutaraldehyde, both porcine and pericardial, have been available as second-generation prostheses for valve replacement surgery. The performance with regard to structural valve deterioration with the Carpentier-Edwards supra-annular (CE-SAV) porcine bioprosthesis and the Carpentier-Edwards Perimount (CE-P) pericardial bioprosthesis (Baxter Healthcare Corp, Edwards Division, Santa Ana, Calif) was evaluated to determine whether there was a difference in mitral valve repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…The last report on the CE-SAV MVR was in 1999 when Jamieson and international colleagues [7] compared the Vancouver CE-SAV MVR experience to the worldwide experience with the CE-PERIMOUNT MVR. The durability, at 10 years, was different with freedom from SVD diagnosed at reoperation being in favor of CE-P for age groups 51-60, 61-70 and >70 years, as documented in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last report on the CE-SAV MVR was in 1999 when Jamieson and international colleagues [7] compared the Vancouver CE-SAV MVR experience to the worldwide experience with the CE-PERIMOUNT MVR. The durability, at 10 years, was different with freedom from SVD diagnosed at reoperation being in favor of CE-P for age groups 51-60, 61-70 and >70 years, as documented in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, from a multi-center study, Jamieson et al [7] reported on structural valve deterioration (SVD), diagnosed at reoperation, between the CE-PERIMOUNT (CE-P) mitral pericardial bioprosthesis and the CE-SAV mitral porcine bioprosthesis. This study identified an inherent superiority of the CE-P but the failure modes of the two bioprostheses, necessitating intervention, were not taken into consideration; predominantly calcific stenosis of the CE-P and regurgitant failure of the CE-SAV.…”
Section: Introductionmentioning
confidence: 99%
“…reported freedom from SVD at 5, 10, and 15 years to be 99%, 94%, and 77%, respectively. Jamieson et al [50] reported that 10 years after-implantation, the incidence of SVD was more in CE porcine valve (CE-SAV) as compared to the CEP valve, which could be due to low commissural region stress in CEP valve. Butany et al have reported that the incidence of SVD was much higher in ISLP valves (71% at, 2-5 years after implantation) and in Hancock II porcine valves (56% at, 5.1 years post implant) [28,51] as compared to the CEP valves.…”
Section: Carpentier Edwards Perimount (Cep)mentioning
confidence: 99%
“…Mechanical valves lead to a persistent need for anticoagulation therapy, and despite some positive reports in the literature, have generally been associated with pulmonary thromboembolic complications [10, 11]. In our institution we have utilized bovine pericardial valves for pulmonary valve replacement because of the superior long-term outcomes of these valves in the aortic and mitral positions and because of the promising early results with their use in the pulmonary position [12, 13, 14]. …”
mentioning
confidence: 99%